2011
DOI: 10.4038/josuk.v3i0.2736
|View full text |Cite
|
Sign up to set email alerts
|

Study on approaches to integrated control of <i>Meloidogyne graminicola</i> in rice

Abstract: This study presents the results obtained from the studies carried out to find out the response of Meloidogyne graminicola to different rice varieties and to different soil amendments when applied with and without NPK fertilizer in young rice plants.The use of soil amendments such as poultry manure and cow dung significantly reduced the nematode population, the total percentage of yellow leaves and dead leaves and significantly increased the plant growth. This study also revealed that the young plants of suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
3
5
0
Order By: Relevance
“…Our data clearly show that also during this early plant growth stage, M. graminicola significantly can reduce these plant growth parameters in the most commonly grown lowland and upland rice varieties in Myanmar. Our data confirm previous studies (Soomro & Hague 1992, 1994Amarasinghe et al 2007;De Waele et al 2013) that reported a similar effect of M. graminicola infection on the early growth of rice plants.…”
Section: Discussionsupporting
confidence: 95%
“…Our data clearly show that also during this early plant growth stage, M. graminicola significantly can reduce these plant growth parameters in the most commonly grown lowland and upland rice varieties in Myanmar. Our data confirm previous studies (Soomro & Hague 1992, 1994Amarasinghe et al 2007;De Waele et al 2013) that reported a similar effect of M. graminicola infection on the early growth of rice plants.…”
Section: Discussionsupporting
confidence: 95%
“…Thus high rate of poultry manure and lower rate of rapeseed cake have been required to bring down the population density of root knot nematode. The results of this study corresponds with Amarasinghe et al (2007) who reported that the lowest nematode population and gall indices were recorded for rice amended with poultry manure. Similarly, Ogwulumba et al (2010) reported that soil amended with organic materials (poultry droppings, grass ash and rice husk ash) at the range of 10 to 20 ton/ha significantly reduced the population of Meleoidogye spp in tomato in Nigeria.…”
Section: Effects Of Poultry Manure and Rapeseed Cake On Rootknot Nemasupporting
confidence: 73%
“…Similar results have been obtained using same treatments tested against M. graminicola in another experiment (Amarasinghe et al, 2007). The present study confirms the results obtained previously.…”
Section: Experiments Ii: Effects Of Soil Amendments and Cinnamon Leaf supporting
confidence: 93%